Infinitely many solutions for perturbed impulsive fractional differential systems. Issue 8 (11th June 2017) - Heidarkhani, Shapour; Zhao, Yulin; Caristi, Giuseppe; Afrouzi, Ghasem A.; Moradi, Shahin
Abstract : In this paper, the existence of infinitely many solutions for perturbed systems of impulsive non-linear fractional differential equations including Lipschitz continuous non-linear terms is discussed. The approach is based on variational methods. In addition, examples are presented to illustrate the feasibility and effectiveness of the main results.